2010
DOI: 10.1016/j.gene.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of alternative splicing of the chi2 chitinase gene from Metarhizium anisopliae

Abstract: Metarhizium anisopliae is a filamentous fungus used in the biological control of arthropods and produces several chitinases in order to break the host cuticle chitin fibers. Chitinase function during fungal cell development and/or infection processes is also an important aspect when analyzing the life cycle of entomopathogens. The expression profile analysis of the endochitinase chi2 gene acquired by RT-PCR experiments indicated the presence of two different transcripts, suggesting the occurrence of alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Conidia presented only four detectable chitinase transcript species ( chimaA7 , A8 , B4 and MaEng18B ). As previously reported [59], the chimaB1 gene ( chi2 ) presented two forms of transcripts that could be detected in MCc, GlcNAc, autolysis and blastospore-inducing conditions. Moreover, two other chitinase genes ( chimaA2 and chimaB 2) presented more than one potential transcript.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Conidia presented only four detectable chitinase transcript species ( chimaA7 , A8 , B4 and MaEng18B ). As previously reported [59], the chimaB1 gene ( chi2 ) presented two forms of transcripts that could be detected in MCc, GlcNAc, autolysis and blastospore-inducing conditions. Moreover, two other chitinase genes ( chimaA2 and chimaB 2) presented more than one potential transcript.…”
Section: Resultssupporting
confidence: 72%
“…The high positional conservation of introns shared by ChiMaA5 and A7 agrees with the OrthoMCL analysis of orthologs and paralogs and classifies these two chitinases as paralogous. Because ChiMaB1 exhibited two transcripts characterized by the removal or retention of the second intron [59], we examined the intron content of ChiMaA2 and ChiMaB2, which presented two bands in RT-PCR experiments (Figure 1). There is an in-frame stop codon at the beginning of the third intron on ChiMaA2, and this could lead to a smaller transcript while not altering the composition of domains in this protein as suggested for ChiMaB1.…”
Section: Discussionmentioning
confidence: 99%
“…The search for chitinases involved in virulence can be based on an analysis of their sequence similarity because phylogenetically related fungal chitinases have been associated with similar functions, and group B chitinases have been implicated in the degradation of chitin from extracellular sources (Seidl et al 2005). Considering that both the chi2 and chi3 genes cluster with the subgroup B chitinases and that the lack of CHI2 chitinase reduces the virulence of Metarhizium anisopliae ( Boldo et al 2010), it is therefore reasonable to consider that the CHIT30 chitinase might also contribute to the M. anisopliae infectious process. In addition, the immunolocalization of this protein to host cuticle regions that surround the invading hyphae strongly suggests that CHIT30 production is associated with penetration (da Silva et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of this gene, however, did not confer increased virulence to M. anisopliae but induced the early production of chitinases under inducing conditions relative to the wild type (WT) strain (Screen et al 2001). The gene chi2 produces two transcripts that undergo alternative splicing via intron retention to produce two proteins (Boldo et al 2010). Moreover, assays using chi2 gene deletion mutations and overexpression to evaluate the contribution of this gene product to the virulence of M. anisopliae against the insect Dysdercus peruvianus have indicated that there is a strong correlation between the M. anisopliae CHI2 chitinase levels and virulence (Boldo et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…chi2, chitinase in Metarhizium anisopliae). 20) Stability of intron retention mRNA of ocpG observed in the fungal cells also raises the possibility that translation could occur from incomplete mRNA. However, the intron retention causes the translation of the defective enzyme by the stop codon in the intron sequence.…”
Section: Intron Retention Might Controls Carboxypeptidase Activitymentioning
confidence: 99%